2013
DOI: 10.1103/physrevlett.110.093001
|View full text |Cite
|
Sign up to set email alerts
|

Water Dimer Rotationally Resolved Millimeter-Wave Spectrum Observation at Room Temperature

Abstract: Water dimers (H(2)O)(2) are believed to affect Earth's radiation balance and climate, homogeneous condensation, and atmospheric chemistry. Moreover, the pairwise interaction which binds the dimer appears to be of paramount importance for expounding a complete molecular description of the liquid and solid phases of water. However, there have been no secure, direct observations of water dimers at environmentally relevant temperatures despite decades of studies. We report the first unambiguous observation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 28 publications
2
59
0
7
Order By: Relevance
“…Finally, recent laboratory studies have resulted in unambiguous detection of H 2 O dimer absorption in the millimeterwave range (Tretyakov et al, 2013;Serov et al, 2014) and to the development of a model to describe it . This absorption shows spectral variation on scales that are not accounted for in the current version of MT_CKD or in Liebe-based models.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…Finally, recent laboratory studies have resulted in unambiguous detection of H 2 O dimer absorption in the millimeterwave range (Tretyakov et al, 2013;Serov et al, 2014) and to the development of a model to describe it . This absorption shows spectral variation on scales that are not accounted for in the current version of MT_CKD or in Liebe-based models.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…More recently, some of this effort was focused on potential atmospheric impact of the water dimer (e.g., Refs. [16][17][18][19]. Most laboratory experiments concentrated on the lower spectral energy ranges.…”
mentioning
confidence: 99%
“…A field measurement by near-infrared spectroscopy has revealed a relatively high concentration of 6 × 10 14 molecules cm −3 of water dimer in the atmosphere. 37,38 9-Nitroanthracene is one of the most abundant nitro-PAHs in the atmosphere. It has been suggested that 9-nitroanthracene cannot be formed from the OH or NO 3 radical-initiated gasphase reaction of anthracene due to the reason given above, and the presence of 9-nitroanthracene in the atmosphere is from a combination of primary emissions and heterogeneous reactions.…”
mentioning
confidence: 99%